Refleksi Matematika Ekonomi Dan Etika Spiritual : Kabataku (Kali, Bagi, Tambah, Kurang) Sebagai Metafora Kebahagiaan Dalam Perspektif Islam - Yandrizal Yandrizal; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Happiness in Islam is not merely understood as material satisfaction, but rather as a state of balance between spiritual, social, and economic aspects. This article aims to examine the concept of happiness through a metaphorical approach using four basic mathematical operations, namely multiplication, division, subtraction, and addition (KABATAKU), from the perspective of Islamic teachings. The method used is a qualitative-descriptive study based on literature reviews of primary Islamic sources, such as the Qur'an and hadith, as well as the works of classical and contemporary scholars. The results of the study show that the multiplication operation represents the multiplication of good deeds, the division operation reflects the principle of distributive justice, the subtraction operation signifies the control of desires, and the addition operation describes the improvement of self-quality through knowledge and worship. These four principles, when applied in a balanced manner, form a framework of ethics in life that can produce individual happiness and social welfare in a sustainable manner. This article emphasizes that the KABATAKU approach is not merely a mathematical analogy, but a practical reflection of Islamic values in modern life.